Modeling the Release of Nitrogen from Controlled-Release Fertilizer with Imperfect Coating in Soils and Water - Trinh, T.H. (American Chemical Society, 2015)
Urea is vulnerable to losses from volatilization or leaching when applied to soils. This study proposes a porous model that couples the interfacial area ratio (IAR) equation for the diffusion of nitrogen with mass transport equation in porous medium (soil). The model presents the release of a single granule with an imperfect coating thickness in different environments. The model is validated with experiments in water and soil environments. In addition, it is compared to our previous model and shows an enhancement in its predictive ability because the imperfection of the coating layer has been integrated in the model. On the basis of the proposed model, the influence of coating variation and soil types also are investigated. In general, simulation results suggest that the coating layer imperfection leads to earlier and faster nitrogen release than an ideal one. Also, nitrogen release in soil depends on soil characteristics such as surface area, particle size, and density. The comparison with experimental observations taken from the literature has validated the model's prediction of nitrogen release in different soil types. Finally, the model has an advantage that it can model the nitrogen release either in water or soil environments. By using the input from the experimental data for the release in water, the release in soil is extrapolated based on the specific soil properties, which can be obtained from experiments or the literature. Â© 2015 American Chemical Society.